DEVELOPMENT LEARNING MEDIA OF MATH-CHA TO SUPPORT VOCATIONAL HIGH SCHOOL REVITALIZATION - Rachmawati Rachmawati; Rina Wijayanti; Era Dewi Kartika (UNIVERSITAS MUHAMMADIYAH METRO, 2020)
The purpose of this study is to produce character building learning media based on m-learning mathematics with a contextual approach that is expected to provide convenience for students and teachers in supporting the revitalization of vocational education. This research is a development research. This research method refers to the 4D development model (Define, Design, Develop, and Disseminate). Development of Math-Cha applications with the help of Android Studio IDE software, and Fire Base. The result of the development in the form of a learning media product is the Math-Cha application which is installed on an Android device. The Math-Cha application consists of material and evaluation. The m-learning media on mathematics is given reinforcement by integrating character education and contextual presentation so that it supports the revitalization of vocational education. Content in the application begins by introducing character values into mathematical problems at the apperception, material and evaluation stages. Evaluation of validity aspects is based on the validation of media experts and material experts who are valid criteria with an average of 3.61. The evaluation of practicality aspects based on student response questionnaire was in the good criteria of 3.72 and the teacher's questionnaire in the criteria of good was 3.40. The assessment of effectiveness aspects based on student test results is in good criteria with an average of 86.6. Math-Cha supports learning, use easily, and it can be used anywhere and anytime.AbstrakTujuan penelitian ini untuk menghasilkan produk media pembelajaran matematika m-learning berbasis pendidikan karakter dengan pendekatan kontekstual yang diharapkan memberikan kemudahan siswa dan guru dalam menunjang revitalisasi pendidikan SMK. Penelitian ini merupakan penelitian pengembangan. Metode penelitian ini mengacu pada model pengembangan 4D (Define, Design, Develop, dan Disseminate). Pengembangan aplikasi Math-Cha dengan bantuan software Android Studio IDE, dan Fire Base. Hasil dari pengembangan berupa produk media pembelajaran yaitu aplikasi Math-Cha yang terinstall di perangkat Android. Aplikasi Math-Cha terdiri dari materi dan evaluasi. Media pembelajaran m-learning pada matematika diberikan penguatan dengan mengintegrasikan pendidikan karakter dan disajikan secara kontekstual sehingga mendukung revitalisasi pendidikan vokasi. Konten dalam aplikasi dimulai dengan mengenalkan nilai-nilai karakter kedalam permasalahan matematika pada tahap apersepsi, materi dan evaluasi. Penilaian aspek kevalidan berdasarkan penilaian validator ahli media dan ahli materi yang berada pada kriteria valid dengan rata-rata 3,61. Penilaian aspek kepraktisan berdasarkan angket respon siswa berada pada kriteria baik sebesar 3,72 dan angket respon guru yang berada dalam kriteria baik sebesar 3,40. Penilaian aspek keefektifan berdasarkan hasil tes siswa berada pada kriteria baik dengan rata-rata 86,6. Math-Cha mendukung dalam pembelajaran, tingkat penggunaannya relatif mudah, pembelajaran dapat digunakan dimana saja dan kapanpun.